2007
DOI: 10.1242/dev.02752
|View full text |Cite
|
Sign up to set email alerts
|

Sperm binding to the zona pellucida is not sufficient to induce acrosome exocytosis

Abstract: At fertilization, spermatozoa bind to the zona pellucida (ZP1, ZP2, ZP3) surrounding ovulated mouse eggs, undergo acrosome exocytosis and penetrate the zona matrix before gamete fusion. Following fertilization, ZP2 is proteolytically cleaved and sperm no longer bind to embryos. We assessed Acr3-EGFP sperm binding to wild-type and huZP2 rescue eggs in which human ZP2 replaces mouse ZP2 but remains uncleaved after fertilization. The observed de novo binding of Acr3-EGFP sperm to embryos derived from huZP2 rescue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 78 publications
3
99
1
1
Order By: Relevance
“…From our perspective, any model for acrosomal exocytosis must take into account the microenvironment at the site of spermzona pellucida interaction as well as the nature of the acrosomal matrix. For example, several studies have noted that GFP loss from the acrosomes of transgenic sperm on the zona is slow and interpret this to mean that acrosomal exocytosis has not occurred (Baibakov et al, 2007, Nakanishi et al, 1999. However, we have demonstrated an intermediate of mouse acrosomal exocytosis in which GFP-transgenic mouse sperm have exposed acrosomal matrix material (as demonstrated by the binding of beads coated with anti-sp56 antibodies) but still retain GFP in their acrosomes (Kim and Gerton, 2003).…”
Section: Role Of Zp In Acrosome Interactionsmentioning
confidence: 69%
See 1 more Smart Citation
“…From our perspective, any model for acrosomal exocytosis must take into account the microenvironment at the site of spermzona pellucida interaction as well as the nature of the acrosomal matrix. For example, several studies have noted that GFP loss from the acrosomes of transgenic sperm on the zona is slow and interpret this to mean that acrosomal exocytosis has not occurred (Baibakov et al, 2007, Nakanishi et al, 1999. However, we have demonstrated an intermediate of mouse acrosomal exocytosis in which GFP-transgenic mouse sperm have exposed acrosomal matrix material (as demonstrated by the binding of beads coated with anti-sp56 antibodies) but still retain GFP in their acrosomes (Kim and Gerton, 2003).…”
Section: Role Of Zp In Acrosome Interactionsmentioning
confidence: 69%
“…A recent paper published by Baibakov et al (2007) challenges some aspects of the current model for events at the interface of the sperm and the zona pellucida. They showed that transgenic mouse sperm adhering to the zona of mouse eggs retained green fluorescent protein (GFP) for an extended period of time and proposed that sperm binding is not sufficient to induce acrosome exocytosis.…”
Section: Role Of Zp In Acrosome Interactionsmentioning
confidence: 99%
“…Despite the widely accepted idea that sperm binding to zona induces acrosome reaction, zona-binding spermatozoa had intact acrosome and did not acrosome react by binding to zona [4,41]. This was reinforced by a recent study observing the fertilization process in vitro using spermatozoa having acrosomal GFP.…”
Section: Zona-induced Acrosome Reaction Must Be Reconsideredmentioning
confidence: 99%
“…A primary functional assay is the human zona-binding test. Whilst the paradigm of sperm binding and subsequent acrosome reaction may be questioned in mice, 24 consistently, robust clinical data demonstrates its usefulness for ART success. A large range of patients have been identified with poor or adequate binding but minimal induction of the acrosome reaction in response to the zona.…”
Section: Sperm Dysfunction-old Tests Lying Dormant?mentioning
confidence: 99%